2008
DOI: 10.1166/jnn.2008.125
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Ordering in Layer-by-Layer Polyelectrolyte Films Studied by Sum-Frequency Vibrational Spectroscopy: The Effects of Drying Procedures

Abstract: Sum-Frequency Vibrational Spectroscopy (SFVS) has been used to investigate the effect of nitrogen-flow drying on the molecular ordering of Layer-by-Layer (LbL) films of poly(allylamine hydrochloride) (PAH) alternated with poly(styrene sulfonate) (PSS). We find that films dried by spontaneous water evaporation are more ordered and homogeneous than films dried by nitrogen flow. The latter are quite inhomogeneous and may have regions with highly disordered polymer conformation. We propose that drying by spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 12 publications
4
25
0
3
Order By: Relevance
“…The samples dried under room conditions seem to be more homogeneous than those dried under vacuum or by nitrogen flow [28]. Silva et al [29] show that the hydrocarbon chains are more ordered using spontaneous water evaporation than those dried by nitrogen flow. They suggested that the spontaneous water evaporation reduces the effect of dragging by the drying front.…”
Section: Depositionmentioning
confidence: 99%
“…The samples dried under room conditions seem to be more homogeneous than those dried under vacuum or by nitrogen flow [28]. Silva et al [29] show that the hydrocarbon chains are more ordered using spontaneous water evaporation than those dried by nitrogen flow. They suggested that the spontaneous water evaporation reduces the effect of dragging by the drying front.…”
Section: Depositionmentioning
confidence: 99%
“…After washing the substrate with an aqueous solution (usually of the same pH as the adsorption solution) in order to remove excess adsorbed material and to ensure that only one strongly adsorbed monolayer remains, the substrate is dried by N 2 flow. We have shown that this drying step promotes the inhomogeneity of the film in the micrometer scale [34], making it unfit for certain applications. The next step is immersing the substrate with the first adsorbed layer in an oppositely charged polyion solution.…”
Section: Layer-by-layer Thin Filmsmentioning
confidence: 99%
“…Considering this throughput limitation, a few alternative methods such as spray-assisted LbL assembly and spin-assisted LbL assembly have been suggested toward developing more rapid and straightforward processing. [5][6][7] In particular, the spinassisted LbL assembly using a highly applied shear force has been extensively investigated due to its advantages in alleviating surface roughness and interpenetration, as compared to the dipping-based LbL assembly. [7][8][9] Another notable aspect of the LbL self-assembly is that it usually leads to a linear growth in film thickness as exemplified in the case of many strongly charged polyelectrolyte multilayer systems.…”
Section: Introductionmentioning
confidence: 99%